Thrombocytopenia as a Predictor of Mortality in Neonatal Pulmonary Haemorrhage: A Cohort Study from a Tertiary Hospital in Bangladesh - Liza, Sumaiya; Talukder, Dite; Roy, Tapan Chandra; Khan, Md Tanvir Hossain (Journal of Rangpur Medical College, 2026)
Background: Neonatal pulmonary haemorrhage carries a high fatality risk, and simple prognostic markers are crucial in low-resource environments. Objective: This study assessed whether thrombocytopenia predicts mortality among affected neonates in a tertiary hospital in Bangladesh. Methods: A prospective cohort of seventy neonates with pulmonary haemorrhage, admitted between July 2019 and June 2021, was evaluated. Platelet counts were recorded at admission and monitored every 12 hours; thrombocytopenia was defined as <150,000/μL. Mortality during hospitalization served as the primary outcome. Results: Overall mortality reached 88.6%. Non-survivors had markedly lower platelet levels than survivors, and this difference was statistically significant. Regression analysis confirmed that thrombocytopenia is an independent predictor of mortality. Survivors also exhibited an earlier onset of haemorrhage compared with non-survivors. Conclusion: Routine platelet assessment provides a practical, accessible prognostic measure and underscore the need for standardized transfusion and monitoring strategies to improve survival. J Rang Med Col.2026 Mar;11(1): 153-158